How and why small volcanic ocean islands collapse and move vertically up and down - Fernando O. Marques; Luísa P. Ribeiro; Christian Hübscher; Ana C. G. Costa; Anthony Hildenbrand (Scientific Reports)
Abstract Mass controls two major processes in volcanic islands: large-scale collapse and vertical movements. Therefore, large islands like Hawaii are gradually subsiding and have undergone massive landsliding. What if the mass is much smaller, and there is good evidence that the vertical movement is more complex than simple loading-related subsidence? Here, we show that small volcanic islands, seemingly stable because of the small mass, can undergo sector collapses that can affect the vertical movement of the island. Santa Maria Island (Azores) is ca. 170 times smaller than Hawaii; however, it has collapsed more than once, as inferred from new onshore and marine geophysical data. From the vertical distribution of submarine and subaerial lavas, we can infer a complex subsidence and uplift history (seamount-island-seamount-island, meaning that Santa Maria has been an island twice), which is most likely the consequence of alternating volcanic construction (loading = subsidence) and large-scale destruction by sector collapse (unloading = uplift). Given the age difference between Santa Maria and the underlying oceanic crust, the island likely sits on several hundred meters of marine sediments that could behave as a weak layer (detachment) under shear. We evaluate the likely collapse mechanism by numerical modelling and conclude that small volcanic islands can collapse when both the edifice and its substrate are weak. The proximity of Santa Maria to the East Azores Fault, active during the volcanic lifetime of Santa Maria, may point to the trigger mechanism of the flank collapses. The inferred instability factor, a weak substrate, could be responsible for similar evolutions in other volcanic ocean islands sitting on sediments overlying the igneous oceanic crust.